2015
DOI: 10.1103/physreva.92.033802
|View full text |Cite
|
Sign up to set email alerts
|

Single pairs of time-bin-entangled photons

Abstract: Original citationVersteegh, M. A. M., Reimer, M. E., van den Berg, A. A., Juska, G., Dimastrodonato, V., Gocalinska, A., Pelucchi, E. and Zwiller, V. (2015) ' Time-bin-entangled photons are ideal for long-distance quantum communication via optical fibers. Here we present a source where, even at high creation rates, each excitation pulse generates, at most, one time-bin-entangled pair. This is important for the accuracy and security of quantum communication. Our site-controlled quantum dot generates single p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…Beside the near-optimal level of entanglement and indistinguishability of the emitted photons, our QDs emit in the spectral range of absorption resonances of rubidium atoms, a system which has proven its potential as long-lived and efficient quantum memory 45 . Moreover, the availability of downconversion techniques 46 in combination with methods to convert polarization entanglement into time-bin entanglement 47 48 make our QDs suited for quantum communication at telecom wavelengths. A key ingredient to achieve high single-photon purity, high two-photon interference and high level of entanglement is the two-photon resonant excitation.…”
Section: Discussionmentioning
confidence: 99%
“…Beside the near-optimal level of entanglement and indistinguishability of the emitted photons, our QDs emit in the spectral range of absorption resonances of rubidium atoms, a system which has proven its potential as long-lived and efficient quantum memory 45 . Moreover, the availability of downconversion techniques 46 in combination with methods to convert polarization entanglement into time-bin entanglement 47 48 make our QDs suited for quantum communication at telecom wavelengths. A key ingredient to achieve high single-photon purity, high two-photon interference and high level of entanglement is the two-photon resonant excitation.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, intense research efforts using InAs semiconductor QDs have enabled the generation of triggered photon pairs at * mullera@usf.edu high rates and under electric pump in a monolithic semiconductor chip with a high degree of polarization entanglement [23,24]. Recently it was shown that such polarization entanglement can be converted into time-bin entanglement, with the polarization entanglement derived from the biexciton/exciton three-level system [25,26].…”
mentioning
confidence: 99%
“…Direct timebin-encoded entanglement generation from quantum dots has the advantage that larger FSSs are acceptable [37] but this scheme cannot produce true on-demand entangled pairs without the addition of a metastable state [37,38] and is technically demanding due to the need for phase control between the early and late photons, which can only be achieved with resonant two-photon excitation [39,40]. Alternatively, in the approach favored here, qubit transcoder setups using asymmetric Mach-Zehnder interferometers (AMZIs) can be used to create timebin-entangled photons from polarization-entangled ones [41,42]; however, demonstrations of this principle using C-band QDs are still outstanding.…”
Section: Introductionmentioning
confidence: 99%